Musik K-Pop dalam Perspektif Kajian Budaya - Arimbi, Afifah; Sepfindra, Rizka; Sunwa, Assyfa Afni; Hidayatullah, Riyan (Journal of Music Science, Technology, and Industry, 2025)
Purpose: This study aims to analyze the phenomenon of K-Pop music from a cultural studies perspective, particularly in relation to consumer culture among fans. In this context, K-Pop music is not only positioned as entertainment, but also as a form of cultural construction that influences the consumption patterns and lifestyles of fans. Method: This study uses a qualitative approach with data collection techniques through literature review, semi-structured interviews, and the distribution of questionnaires to active students who follow K-Pop developments. Literature data was obtained from academic journals, reference books, and relevant and credible sources to strengthen the analytical framework. This study applies triangulation techniques as a method of processing the data obtained. Result and Discussion: The study shows that support for K-Pop music is an initial representation of fans' emotional loyalty, which gradually develops into consumption patterns that are ingrained in their identity, such as purchasing products released by K-Pop idols and adopting a Korean lifestyle. These findings reveal that the consumerist culture within the K-Pop fan community is not limited to economic aspects but also reflects social and symbolic dynamics among teenagers and young adults, particularly K-Pop fan students. Implication: In the era of globalization, technology is a necessity, including the need for musical artists or musicians to realize their works. The realization of musical works can be done through recording and performance activities. MIDI, as a technological product, can be a solution for composers and musicians in creating musical works. MIDI can make the process of recording and performing musical works effective and efficient.